Determination Of Applicable Law In Mixed Marriages : Analysis Of The Principle Of Choice Of Law In The Indonesian Legal System ( A Study Of How Indonesian Law Determines The Applicable Jurisdiction In Mixed Marriages Based On Law No.1 Of 1974 And Internat - Abdurahman, Abdurahman; Basit, Abdul; Al Amruzi, M. Fahmi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
This study analyzes the applicable law in mixed marriages in Indonesia, focusing on choice of law principles in national and international law. Using normative juridical methods, it examines jurisdictional issues under Law No. 1/1974 and international law, finding that lex loci celebrationis and parties' national laws determine validity. The study highlights the need for legal harmonization to ensure protection and justice.